2015
DOI: 10.1136/jfprhc-2015-101244
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards abortion in graduate and non-graduate entrants to medical school in Ireland

Abstract: The majority of students, regardless of mode of entry, believed abortion was justified where there was a real risk to the life of the mother (including risk of suicide) or in cases of fetal non-viability. The most significant determinant of students' beliefs was religious adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Another factor influencing agreement for abortion was religious affiliation and values. 5,[42][43][44] O'Grady et al 45 concluded that religious adherence was the strongest determinant of an Irish medical student's perspective on the ethics of abortion.…”
Section: Abortionmentioning
confidence: 99%
“…Another factor influencing agreement for abortion was religious affiliation and values. 5,[42][43][44] O'Grady et al 45 concluded that religious adherence was the strongest determinant of an Irish medical student's perspective on the ethics of abortion.…”
Section: Abortionmentioning
confidence: 99%